SISTEM INFORMASI BERBASIS KOMPUTER SEBAGAI PENDUKUNG KEPUTUSAN PEMILIHAN PEJABAT MENGGUNAKAN METODE AHP - yahfizham yahfizham (UIN Sumatera Utara, 2014)
The issue of election officials to occupy a strategic position became the deep concern. It is common knowledge that if you want to become officers must spend some money, ethnicity, and proximity (